Informator . no. 40, 1981 - "Solidarność" Biuro Informacyjne Zarządu Regionu Środkowo-Wschodniego, [ed. W. Samoliński, W. Jackson, J. Staworko] (NSZZ "Solidarność" Region Środkowo-Wschodni, 1981)
Creation and circulation: For trade-union use; After introduction of the Martial Law publication suspended. Republished underground in January 1982